Competitive diving principles and injuries - Jones, N. S. (Current Sports Medicine Reports, 2017)
Competitive diving is a sport that has evolved over time to become an admired present-day aquatic sport, especially in the Olympic setting. Despite its popularity, sparse research has been written as it applies to our understanding of competitive diving injuries. This article attempts to discuss common principles of competitive diving as they relate to the sport, especially as it relates to the extreme physical forces encountered by the diver and also the repetitive nature of diving. Next, these principles will be applied in the context of musculoskeletal and medical diving specific injuries.